Valoración de la incidencia y severidad de pulgón y trozador bajo dos sistemas de irrigación parcelaria en el cultivo de brócoli (Brassica oleracea var. itálica) en Laguacoto I, cantón Guaranda, provincia Bolívar - Ramírez Cando, Juan Gabriel (2024)
Broccoli production in Ecuador is located in an area of approximately 9000 hectares, of which 5000 m2 is located in the province of Bolívar on a temporary basis in family gardens. Broccoli production in the Guaranda canton has shown low productivity due to the low availability of water for irrigation, prolonged periods of drought, which have caused a nutritional imbalance in the plant, facilitating the presence of pests such as aphids and leafhoppers. The objectives set in this essay were; determine the incidence and severity of aphids and cutworms; establish the influence of two plot irrigation systems on pest control; evaluate in which of the two plot irrigation systems the highest incidence of aphids was obtained. The present investigation was carried out in Laguacoto I, the experimental material used was: two irrigation systems: sprinkling and drip; Broccoli plants, Avengere hybrid. The factor under study was represented by the irrigation system. Among the statistical tests are: means, minimum, maximum and the dependent T test to compare averages; The results obtained were the following: The incidence of aphids in the broccoli crop was; fifteen%; 40% and 60% at 30, 60 and 90 days, the cutter recorded a reading of 38.4% for T2. While T1 had 25%; 55%, 68% respectively and the chopper had 45.1%. In a similar response, the severity was quantified at 17.6%, 38.3%, 59.9% for T2 and 18.3%, 39.7% and 62.2% in T1 at 30, 60 and 90 days respectively. The chopper for this variable recorded a value of 0%. There was no evidence of influence of the two irrigation systems in terms of pest control at 30, 60 and 90 days. This result is due to the effect of high levels of aluminum ion in the soil, which caused toxicity in plants, especially roots, which limited the absorption of water and nutrients. The highest incidence rate of aphids in the broccoli crop was presented by the drip irrigation system (T1) with 25%; 55% and 68% at 30 days, 60 days and 90 days respectively.